Two diode model for parameters extraction of PV module - Shannan, N.M. (Institute of Electrical and Electronics Engineers Inc., 2014)
This paper introduces an improved two-diode model of photovoltaic (PV) module. The main influence of this work is the combination of the accuracy of the two diode model and the short computational time of the single diode model. The proposed model is validated against various types of PV modules (mono-crystalline, multi-crystalline, and thin-film) from a variety of manufacturers. The model performance is evaluated against the famous single diode model and the two diode model. The model proves its superiority when exposed to variation in temperature, as it matches accurately for all important points of the I-V curve. Â© 2014 IEEE.